Algorithm of global uniformization of algebraic correspondence - Dolgopolova, O. B.; Zverovich, E. I. (Mathematical Modelling and Analysis, 1998)
The problem of global uniformization of algebraic correspondence is investigated. The weaker assumptions are used in the analysis.First Published Online: 14 Oct 2010